Aprendendo a pertencer: uma leitura da trezena de Santo Antônio em Pradoso enquanto territorialidade humana - Alves, Carley Rodrigues (2010)
The Novena of St. Anthony in Pradoso, is an annual celebration that takes place between June 1 and June 13. Since its preparation to the conclusion of the celebration are employed traditional knowledges and techniques, which are shared by the community. Such knowledges, built over generations, associated with popular religion, form it into the educational processes that build, through orality, practices and experiences of everyday life, the sense of belonging. An analysis of scenes, knowledges and subjects involved in the celebration, shows the form and content of practices capable of building symbolic territories of belonging. Thus, the Novena of St. Anthony in Pradoso, while an human territoriality, is designed as a locus of learning of belonging, reaffirming community values such as solidarity, service, brotherhood, integration, among others. While empirical reference for an analysis of the importance of belonging, the Novena of St. Anthony in Pradoso, offers subsidies for the production of knowledge, focused on understanding the need for a reconnection of technical and humanistic knowledges